A LOOK BACK ON THE VERSE OF PHAN VĂN TRỊ AFTER 130 YEARS - Le Giang Doan (Tạp chí Khoa học Đại học Đà Lạt)
Phan Văn Trị (潘文值1830–?) was a prominent writer in Cochinchina in the late nineteenth century. He achieved the rank of senior bachelor (舉人 cử nhân) in the Confucian court examination at a young age but never joined the imperial bureaucracy. Despite living an agrarian life as a layman, he was popular all over Cochinchina for his talent in poetry creation. When the three provinces of Eastern Cochinchina were taken by the French, Phan Văn Trị led a patriotic writing movement against Tôn Thọ Tường (尊壽祥) and his idea of surrendering to the colonizers. Phan Văn Trị was famous for his polemical poems, object poems, and pastoral poems. This article provides a brief literature review of Phan Văn Trị’s writings, describes the condition of his texts, and evaluates his poetry.